ممارسة النشاط البدني الرياضي ودوره في التخفيف من الضغط النفسي الناتج عن الحجر الصحي لدى تلاميذ المرحلة المتوسطة - بن شيتة, محمد; بن مشيش, عماد الدين (Institut d’Éducation Physique et Sportive mostaganem 2021/2022, 2021)
وتهدف الد ارسة التي بين أيدينا إلى محاولة معرفة دور النشاط البدني الرياضي في التخفيف من الضغط النفسي الناتج عن الحجر الصحي لدى تلاميذ المرحلة المتوسطة ،ولأجل ذلك اتبعنا المنهج الوصفي بالأسلوب المسحي، حيث تكونت عينة الد ارسة من 100 تلميذ وتلميذة، من المجتمع الأصلي الذي يمثل بعض من تلاميذ التعليم المتوسط، وهي عيّنة عشوائية، واستعملنا لجمع البيانات استمارة الاستبيان، واستخدمنا لتحويل البيانات الى نتائج إحصائية معامل )الصدق، الثبات، معامل الارتباط البسيط لبيرسون(، وجاءت أهم نتائج الد ارسة ان عدم ممارسة التلاميذ للنشاط البدني الرياضي أدى الى انعكاس على أفعالهم داخل المؤسسة، وان تنوع الأنشطة البدنية بين تلاميذ المرحلة الثانوية له دور في التقليل من الضغط الذي سببه الحجر الصحي، اما اهم الاقت ارحات والتوصيات فتمثلت بداية بالاهتمام بحصص النشاط البدني الرياضي والممارسة المستمرة، ومحاولة التعرف على أسباب الضغط النفسي لدى التلاميذ. Practicing physical activity and its role in alleviating the psychological stress caused by quarantine among middle school students The study that we have in our hands aims to try to know the role of physical sports activity in alleviating the psychological stress resulting from quarantine among middle school students, and for that we followed the descriptive approach using the survey method, where the study sample consisted of 100 male and female students, from the original community that represents some of the Students of middle education, which is a random sample, and we used a questionnaire form to collect data, and we used to convert the data into statistical results, coefficients (honesty, reliability, Pearson’s simple correlation coefficient), and the most important results of the study were that the students’ lack of physical activity led to a reflection on their actions within the institution. The diversity of physical activities among secondary school students has a role in reducing the stress caused by the quarantine. As for the most important suggestions and recommendations, the beginning was to pay attention to physical activity classes and continuous practice, and to try to identify the causes of psychological stress among students.
LEPS-2022-10
Keywords: : النشاط البدني الرياضي - التخفيف، الضغط النفسي - الحجر الصحي، المرحلة / sports physical activity, mitigation, psychological pressure - quarantine - middle school.